PENINGKATAN KEAKTIFAN SISWA MELALUI MEDIA KONGKRET PAPAN BILANGAN DALAM PEMBELAJARAN MATEMATIKA KELAS II SD - Pingky Citra Inpriani; Tri Masiul Khusna, Yuyun; Septi Tiaradinar; Wahyu Susiloningsih; Menik Rupiati; Darsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student learning activeness through the use of concrete media in the form of a place value board (tens and units) in mathematics learning for second grade students at SDN Dukuh Kupang II-489 Surabaya. This research used a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of two cycles. The research subjects were 28 second-grade students. Data were collected through observation, written tests, and documentation. The results showed that student activeness increased significantly from 25% in the pre-cycle to 59.3% in Cycle I, and further improved to 85.7% in Cycle II, with a total increase of 60.7%. Student learning outcomes also improved, with the average score rising from 61.07 (pre-cycle) to 88.92 (Cycle I) and 96.07 (Cycle II). The percentage of learning completeness increased from 39.3% in the pre-cycle to 85.7% in Cycle I, and reached 100% in Cycle II. These findings indicate that the use of the concrete place value board media is effective in improving student activeness and learning outcomes in mathematics, particularly on the topic of place values, addition, and subtraction.